Mining ice in genomes: comparative genomics of integrative elements in prokaryotic genomes - Quintais, Leonor Maria dos Santos Silva Tomé, 1986- (2011)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2010